Phyllodes tumor and its malignization into invasive ductal carcinoma a case report - Jesenková, A; Mergancová, J; Mergancová, J; Dvořáková, D; Šnáblová, E; Hácová, M (Rozhledy v chirurgii, 2021)
INTRODUCTION: Phyllodes tumors of the breast are rare and very distinct types of mammary neoplasms. They are characterized by their biphasicity, i.e. the presence of stromal and epithelial components at the same time. Malignancy is determined by the degree of stromal differentiation. The coexistence of the malignant epithelial component is a very rare phenomenon. Dozens of cases of simultaneous phyllodes tumor and epithelial malignancy have been reported so far. Nevertheless, the biological nature of this process is still an unexplained and a controversial topic. CASE REPORT: In this paper, we present a case of a patient with a suddenly enlarging lesion in the breast. According to the first surgical resection, a diagnosis of high-grade malignant phyllodes tumor was made with fibrosarcoma differentiation, stromal overgrowth and suppression of the epithelial component. Examination of scar resistence in early postoperative period revealed a triple-negative invasive low-differentiated breast carcinoma with very high proliferative activity, thus malignization of the epithelial component of the tumor occurred. Shortly, a diagnosis of second recurrence was made, treatment included axillary lymph node dissection (ALND) with a negative histological findings. The patient underwent complex adjuvant chemotherapy and radiotherapy and remained disease free 3 years after the surgery. CONCLUSION: Coexistence of phyllodes tumor and the breast carcinoma is very rare. The article describes the first published case, which documents the subsequent development of invasive low-differentiated ductal carcinoma immediately after resection of high-grade phyllodes tumor. Treatment and prognosis are generally determined by the characteristics of the carcinomatous component.
Keywords: breast cancer; duktální karcinom; case report; lokální recidiva nádoru; breast neoplasm; Phyllodes Tumor; nádory prsu; cystosarcoma phyllodes; Breast; Neoplasm Recurrence, Local; ductal carcinoma; lidé; Carcinoma, Ductal; ženské pohlaví; Breast Neoplasms; Humans; phyllodes tumor; prsy; Female